Proceedings of the 16th ACM Symposium on Virtual Reality Software and Technology 2009
DOI: 10.1145/1643928.1643941
|View full text |Cite
|
Sign up to set email alerts
|

Gaze behavior and visual attention model when turning in virtual environments

Abstract: In this paper we analyze and try to predict the gaze behavior of users navigating in virtual environments. We focus on first-person navigation in virtual environments which involves forward and backward motions on a ground-surface with turns toward the left or right. We found that gaze behavior in virtual reality, with input devices like mice and keyboards, is similar to the one observed in real life. Participants anticipated turns as in real life conditions, i.e. when they can actually move their body and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…As future work, Lee et al [6] suggested to take into account the novelty of objects and other adapted top-down components. To this aim, Hillaire et al [7] have studied user's gaze behavior when walking and turning in VEs. They have proposed a new model taking into account first-person navigation in order to compute an attentional weight on the whole screen based on the current rotation velocity of the camera.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…As future work, Lee et al [6] suggested to take into account the novelty of objects and other adapted top-down components. To this aim, Hillaire et al [7] have studied user's gaze behavior when walking and turning in VEs. They have proposed a new model taking into account first-person navigation in order to compute an attentional weight on the whole screen based on the current rotation velocity of the camera.…”
Section: Related Workmentioning
confidence: 99%
“…The gaze behavior of users exploring VEs has been studied in [7] [18]. The top-down component of our visual attention model takes into account the observed gaze behavior resulting from the fact that users are navigating in the VE using a first-person view.…”
Section: Computation Of Statistical Screen-space Componentsmentioning
confidence: 99%
See 3 more Smart Citations